ANTIPYRETIC POTENTIAL OF AQUEOUS LEAF EXTRACT OF ANNONA MURICATA.L AND SPERMACOCE ARTICULARIS. L.F. ON YEAST-INDUCED PYREXIA IN RATS - K, Maruvoor Arasi; C, Krishnaveni (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of this study is to evaluate the potential of in vivo antipyretic activity of the aqueous leaf extracts of Annona muricata L. and Spermacoce articularis. L.f. Methods: The acute oral toxicity was determined by the Organization of Economic and Cooperation Development-423 class methods, and the in vivo antipyretic activity was determined by brewer's yeast induced pyrexia method. Results: The results showed that the aqueous leaf extract of A. muricata. L and S. articularis L.f plants is non-toxic and possessed significant antipyretic effect. Conclusion: This study provides evidence for the antipyretic activity of A. muricata. L and S. articularis L.f. The aqueous leaf extract of S. articularis L.f at a dose of 400 mg/kg showed a more significant effect (p<0.01) in lowering the hypothermia than the extract of A. muricata L but found to have a similar effect as the standard drug aspirin (100 mg/kg).